Analysis of Mathematical Content Knowledge of Elementary Teachers in Lampung Utara Regency: A Baseline Study - Budi Poniam (Program Studi Pendidikan Matematika FMIPA Universitas Negeri Jakarta, 2020)
According to TIMSS 2015 and PISA 2018 reports, Indonesian students’ knowledge and skills of mathematics are still far from adequate compare to other countries. Therefore the efforts to improve the condition need to done, not just by government but also educational institutions and movements. One of new movement is Gerakan Nasional Berantas Buta Matematika (GernasTastaka, 2018). This baseline study aims to describe and analysis the mathematical content knowledge of 100 elementary teachers from Lampung Utara regency that joined the workshop of mathematics teaching and learning which was developed and facilitated by team from Gernas Tastaka. The eight-question multiple choice pre-test covers Number and Operation, Measurement, Data Analysis, and Probability. Each question is related to specific mathematical content knowledge and skill that are supposed to be mastered by grade 6 students. The quantitative descriptive for each question was conducted to give more details on specific mathematical content knowledge. The result displays that only 36% of the participants can answer correctly 50% of the questions. The low competency of teachers gives impact to their students’ achievement. It is correspondent with the data from Indonesian National Assessment Program (INAP, 2012); mathematics competency of elementary students in Lampung province is below Indonesian national level. One of the teachers’ competencies is their mastery of content knowledge. This study recommends that future developmental workshops/ program for the participants must cover all mathematical content knowledge and skills of elementary level. Besides that, detailed data of participants should be provided in order to attain more reliable analysis.